PELAKSANAAN IZIN USAHA MIKRO DAN KECIL (IUMK) GRATIS DI KECAMATAN SUKAJADI KOTA PEKANBARU - Julita, Ami; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The implementation of free Micro and Small Business License (IUMK) in Sukajadi District which entered into force since February 2015 has been applied successfully. The reason behind this is that the government has issued policy to facilitate the administration of Micro and Small Business License (IUMK) from the district head and the urban village head. In line with the mission of the central goverment in simplifying the licensing process, the mayor of Pekanbaru has created free Micro and Small Business License (IUMK) program. This research was done to determine how the implementation of free Micro and Small Business License in Sukajadi District and what factors affect the implementation of IUMK in Sukajadi District.This descriptive research was conducted using quantitative method. This research used the dimensional theory of service quality by Agus Dwiyanto consisting of the attitude of officers, procedures, time, facility, and fee of the service. The techniques used in this research are observation, interview, documentation, and litterature study using descriptive analysis technique.The result of this research revealed that the implementation of Micro and Small Business License (IUMK) in Sukajadi District has been qualified. It was indicated by the officers’ good and friendly attitude, the simple and clear service procedure, the on-time and standardized service completion, and the standardized service fee. Moreover, the existence of apparatus resources and the good awareness from society has made the implementation of free Micro and Small Business License (IUMK) in Sukajadi District becomes successful.Keywords: Implementation, Business License, Service